Pelatihan Pengolahan Buah Pandan Tikar (Pandanus tectorius Park.) menjadi Tepung dan Cookies di Kampung Sidey Baru, Distrik Sidey, Manokwari - Paga', Bertha Ollin; Sarungallo, Zita Letviany; Irbayanti, Diana N.; Sampe, Theresia Tina (Fakultas Peternakan Universitas Papua, 2021)
Sidey Baru is one of the villages located in Manokwari Regency, near the beach and found Pandan Tikar (Pandanus tectorius Park.) plant, which has not been utilized. Pandan Tikar fruit contains good nutrition to be developed as a food ingredient that can increase the added value of the product. This community service activity aims to be able to increase community skills in processing pandan fruit into flour and its derivative products, to be able to meet family needs and can also be marketed to improve the community's economy. This community service activity was carried out in the form of direct training with the people of the village of Sidey Baru, especially women from the PKK organization, business groups, and village officials, with the hope that the community could produce flour and cookies from Pandan Tikar fruits in a sustainable manner so that it could help improve the community's economy. The training on making fruit flour and cookies from pandan mat fruit is very attractive to the people of Kampung Sidey Baru, because the raw materials are easy to obtain and made with simple technology. Overall, participants were able to take part in the training and material training well, so it is hoped that the knowledge and skills gained from the training can be enjoyed by other people. Efforts to increase the added value of Pandan tikar fruit into various highly competitive products can be realized through continuous guidance and assistance by Sidey village officials together with the Faculty of Agricultural Technology, University of Papua.